+0  
 
0
270
2
avatar

Sinh ( 3 x pi xi)

Guest Feb 3, 2015

Best Answer 

 #1
avatar+26406 
+5

sinh(x) = (ex - e-x)/2  so

 

sinh(3*pi*i) = (e3*pi*i - e-3*pi*i)/2

 

Now eiy = cos(y) + i*sin(y) so

 

sinh(3*pi*i) = (cos(3pi)+i*sin(3pi) - cos(3pi)+i*sin(3pi))/2 = i*sin(3pi) = i*0 = 0

.

Alan  Feb 3, 2015
Sort: 

2+0 Answers

 #1
avatar+26406 
+5
Best Answer

sinh(x) = (ex - e-x)/2  so

 

sinh(3*pi*i) = (e3*pi*i - e-3*pi*i)/2

 

Now eiy = cos(y) + i*sin(y) so

 

sinh(3*pi*i) = (cos(3pi)+i*sin(3pi) - cos(3pi)+i*sin(3pi))/2 = i*sin(3pi) = i*0 = 0

.

Alan  Feb 3, 2015
 #2
avatar+81051 
0

Thanks, Alan....I always forget that we can use Euler's "formula" on these...!!!

 

CPhill  Feb 3, 2015

17 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details